Talent Management Strategy to Face the Challenges of the Industrial Revolution 5.0 Era - Tambunan, Hotbona Novandi; Hutasoit, Debri Ton Mario; Julyarman, Nasrun; Nathaniel, Raba; Fakih, Choerul; Pandiangan, Saut Maruli Tua (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The world of work has undergone major changes as a result of the Industrial Revolution 5.0. Organizations and individuals must quickly adapt to the demands of ever-evolving skills and new technologies. The purpose of this study is to investigate talent management strategies that are useful for addressing challenges and capitalizing on opportunities in this era of disruption. The study identifies the latest trends in human resource management and related technologies by reviewing relevant literature. The results show that improving both hard and soft skills is essential. Hard skills, such as the ability to use digital technology and data analysis, are essential to cope with technological change, while soft skills, such as the ability to communicate, collaborate, and lead, are essential to adapt to new work dynamics. Foreign language proficiency is increasingly important if you want to collaborate and compete in the global market. To apply knowledge and acquire relevant skills, practical training is needed, both inside and outside the work environment. By implementing these strategies, companies can maintain their competitiveness and maximize the potential of their employees in the dynamic technological era. To ensure long-term success, companies must adopt a proactive approach to their talent development.